Omega-3-Fortified Lipid-Based Nutrient Supplement: Development, Characterization, and Consumer Acceptability. Issue 2 (June 2017) - Gaur, Shashank; Sloffer, Elizabeth M.; Ojha, Ankur; Patra, Falguni; Shukla, Dharmendra; Engeseth, Nicki J.; Patel, Pramthesh R.; Andrade, Juan E.
Background: Incorporation of omega-3 polyunsaturated fatty acid (PUFA) sources to lipid-based nutrition supplement (LNS) formulations for undernourished populations presents a challenge due to reduced shelf life and poor consumer acceptability. Objective: To systematically develop an omega-3-fortified LNS formulation, using flaxseed oil (FO), by optimizing its processing stability and evaluating its sensory acceptance. Methods: LNS formulations were formulated to yield approximately 452 kcal, 13.2 g of protein, 30 g of fat, and 53 g of carbohydrates per 100 g. Response surface methodology (RSM) with 4-factor-3-level: omega-3 fatty acid source (FO; 0%-10%), antioxidant (ascorbyl palmitate: 0.0%-0.03%), emulsifier (soy lecithin: 0.5%-1.5%), and storage time (0-6 months at 40°C) was used to optimize LNS's functionality and storage stability. Factor effects were evaluated for peroxide value, oil separation, water activity, moisture content, hardness, and vitamin C content of the samples. Consumer acceptability was assessed using a 9-point hedonic scale. Results: After 6 months of accelerated storage, the addition of FO to LNS formula resulted in increased peroxide values (7.75 mEq/kg fat) and lipid separation and a reduction in vitamin C and water activity. Optimal levels to maximize storage time and FO and minimize oxidation were 0.02% antioxidant, 1.5% emulsifier, and 4.9% FO. Indian women and students accepted LNS formulations with or without FO similar to other commercial supplements. Conclusion: An LNS containing FO with improved omega-6/omega-3 PUFA ratio was successfully formulated with staple Indian ingredients and optimized for storage stability using RSM.